(3GdQSGdI GdhGUdIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3jG CNj GdYRjR Ydi CWGd Gddg ai YR GdWGYI HbGc hCOGe MQGSJc ai Ojfc hOfjGc Ydi jO GdCN GdNjQ CHj GdMSf GdeMdi QaY Gddg OQLJg s
(3BNQgG (B:s
(3hEeGe GdhQi GdOGYi Edi NjQ GdYed hGdbGFe Ydi GdfahS HecJSHGJgG hfGSN GdTQGFY hGdedd JeJ hGdMeO dehdGfG hMOg hGdTcQ dbGFe GdReGf YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B108s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis